Phytoplankton photophysiology varies depending on nitrogen and light availability at the subsurface chlorophyll maximum in the northern Chukchi Sea - Ko, Eunho; Gorbunov, Maxim Y.; Jung, Jinyoung; Lee, Youngju; Cho, Kyoung-Ho; Yang, Eun Jin; Park, Jisoo (Frontiers in Marine Science, 2022)
Vertical distributions of phytoplankton in the Arctic Ocean are characterized by a very narrow subsurface chlorophyll maximum (SCM) layer formed every summer after the sea ice retreats. Despite the prevalence of this narrow SCM layer, phytoplankton photosynthetic response to climate change remains to be elucidated. Here, we examined the photophysiological properties of phytoplankton in the SCM layer in the northern Chukchi Sea during the summers of 2015–2018. There was a significant difference in the SCM depth between the northwestern and northeastern Chukchi Sea determined by the distribution of Pacific Summer Water (PSW) around the SCM layer (34 ± 14 m vs. 49 ± 10 m, respectively). The maximum quantum yield of photochemistry in photosystem II (Fv/Fm) in the SCM phytoplankton was high (Fv/Fm ≥ 0.54) and similar in both regions until 2016; however, since then, Fv/Fm in the northeastern Chukchi Sea has decreased by approximately 10%. This decrease was accompanied by a marked decrease in the fraction of microplankton, which are known to be susceptible to nutrient limitation. This result suggests a reduction in nitrogen availability in the SCM layer in the northeastern Chukchi Sea. Meanwhile, the maximum electron transfer rate (ETRmax) did not have a significant relationship with the nitrogen availability and phytoplankton community size structure in the SCM layer; however, the improved light conditions (with an approximately two-fold increase in the relative ratio of surface PAR reaching the SCM layer) increased ETRmax by up to 30% in the SCM phytoplankton in the northwestern Chukchi Sea. Therefore, these results provide a better understanding of how changes in nitrogen and light availability could affect phytoplankton photosynthesis and primary production in the Arctic Ocean.